Foraging ecology of black bears in urban environments: guidance for human-bear conflict mitigation - Lewis, D. L., author; Baruch-Mordo, S., author; Wilson, K. R., author; Breck, S. W., author; Mao, J. S., author; Broderick, J., author; Ecological Society of America, publisher (Colorado State University. Libraries, 2015)
Urban environments offer wildlife novel anthropogenic resources that vary spatiotemporally at fine scales. Property damage, economic losses, human injury, or other human-wildlife conflicts can occur when wildlife use these resources; however, few studies have examined urban wildlife resource selection at fine scales to guide conflict mitigation. We studied black bears (Ursus americanus) in the urban area of Aspen, Colorado, USA from 2007 to 2010 to quantify bear foraging on natural and anthropogenic resources and to model factors associated with anthropogenic feeding events. We collected fine-scale spatiotemporal data by tracking GPS-collared bears at 30-min intervals and backtracked to bear locations within 24 hours of use. We used discrete choice models to assess bears' resource selection, modeling anthropogenic feeding (use) and five associated random (availability) locations as a function of attributes related to temporally changing natural (e.g., ripe mast) and human (e.g., garbage) food resources, urban characteristics (e.g., housing density), and land cover characteristics (e.g., distance to riparian area). We backtracked to 2,675 locations used by 24 bears and classified 20% as foraging locations. We found that bears foraged on both natural and anthropogenic food sources in the urban environment, with 77% of feeding events being anthropogenic. We documented inter- and intra-annual foraging patterns in which bears foraged extensively in urban areas when natural food production was poor, then switched to natural food sources when available. These patterns suggest that bears balance energy budgets and individual safety when making foraging decisions. Overwhelmingly, garbage was the main anthropogenic food source that bears used. Selection of foraging sites was not only influenced by presence of garbage but also by proximity to riparian habitat and presence of ripe anthropogenic fruit trees. We found that while 76% of the garbage containers at random locations were bear-resistant, 57% of these bear-resistant containers were not properly secured. We recommend conflict mitigation focus on reducing available garbage and anthropogenic fruit trees, particularly near riparian areas, to make urban environments less energetically beneficial for foraging. Additionally, deploying bear-resistant containers is inadequate without education and proactive enforcement to change human behavior to properly secure garbage and ultimately reduce human-bear conflict.
Keywords: conflict mitigation; discrete choice models; foraging ecology; garbage management; human-wildlife conflict; resource selection; urban ecology; American black bear; Ursus americanus